Gender implications of illiteracy: Dimension of illiteracy and it’s victims - Šuleić Marijana (Temida, 2013)
In the society we live in today, when human rights are spoken about, the notions of female identity and of female human rights often occupy a large space in the various theoretical debates. One of the reasons for the continued prevalence of such notions is the unequal position of women in the context of gender politics. When we take into account the different contexts in which women live, such as distance from the center, a marginalized position in some cases and a very bad image of education, taking responsibility for building a stable identity becomes one of the most important questions. According to UNESCO reports in 2007, every fourth woman suffers from the consequences of illiteracy, which are more significant in rural areas (UNESCO, 2007). Education still does not have an important place in debates in political circles in spite of efforts invested. The situation becomes more complicated when the lack of gender senstivity in educational policy and stereotypes about female roles in society are added to the existing state of inequality of availability of education, particularly the differences between rural and urban areas. In such circumstances, literacy and education are the most important components of building a stable identity, which includes willingness of women to accept responsibility for different roles that society imposes.